2021
DOI: 10.1186/s12960-020-00540-5
|View full text |Cite
|
Sign up to set email alerts
|

Caring Behaviors Inventory-24: translation, cross-cultural adaptation and psychometric testing for use in a Swedish context

Abstract: Background Patients’ health and wellbeing are promoted when nurses successfully conceptualize caring in clinical practice. Measuring caring behaviors can advance knowledge about caring and has potential to improve caring practices and the outcomes of care. The Caring Behaviors Inventory-24 (CBI-24) is an empirical instrument for measuring caring, developed to determine perceptions of caring among patients and nurses. Since the instrument was not available in Swedish, the aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…With support from the research assistant, the face-to-face data collection occurred at the healthcare centre. Data were collected using pen-and-paper, Swedish versions of the Attitudes Toward Homelessness Inventory (ATHI) [ 32 ] and the Caring Behaviours Inventory-24 (CBI-24) instruments [ 33 ], in addition to general questions about background characteristics. The women were asked to answer the CBI-24 questions according to how they perceived nurses’ caring behaviours at their latest healthcare visit.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…With support from the research assistant, the face-to-face data collection occurred at the healthcare centre. Data were collected using pen-and-paper, Swedish versions of the Attitudes Toward Homelessness Inventory (ATHI) [ 32 ] and the Caring Behaviours Inventory-24 (CBI-24) instruments [ 33 ], in addition to general questions about background characteristics. The women were asked to answer the CBI-24 questions according to how they perceived nurses’ caring behaviours at their latest healthcare visit.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected using the Swedish versions of the CBI-24 and ATHI instruments. Previous studies have indicated that these instruments are psychometrically acceptable for use in Swedish healthcare research [ 32 , 33 ]. Psychometric testing of the reliability and validity of the Swedish version of the ATHI indicates acceptable item reliability [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Promoting comfort includes allowing patients to bring a familiar object. Maintaining the therapeutic relationship includes recognizing verbal and non-verbal messages, and encouraging the patient to initiate a conversation (Akgün et al, 2020;Kibret et al, 2022;Klarare et al, 2021;Salimi & Tarbiat, 2021).…”
Section: Introductionmentioning
confidence: 99%